Pain through climate influence: Prevalence between algic and weather parameters (Research, Society and Development, 2021)
Chronic pain is a relevant public health problem worldwide and the impact of environmental factors, such as the climate, can be great allies in new therapeutic discoveries. Thus, the objective of the study was to elucidate how meteorological parameters act on pain in terms of prevalence and level of influence, from outpatients with different age groups and morbidities. It is a descriptive analytical, cross-sectional and quantitative study, using an elucidated questionnaire. The statistical analysis used was the Linear Correlation e Wilcoxon-Mann-Whitney, T-Student and Chi-square tests. The meteorological data used were taken from the website of Simepar, Parana’s Technology and Environmental Monitoring System. The sample was composed of 96 patients, being 48% hypertensive, 23% diabetic and 66% with some chronic pain. It was observed that 73% of the participants associate climate as an influencing factor in pain, in which 75.71% report being worse on days of sudden cold. The research findings also show that hypertensive patients suffer 4.87% more pain for each 1hPa increase in barometric pressure (95% CI / 0.92 - 8.82). From these results, it is noted that climatic conditions can have a great clinical influence, especially in patients with chronic diseases, despite of the necessity to longitudinal studies for better understanding.